Studi Takhrij Hadis Terhadap Materi Pembelajaran Hadis Pada Siswa Taman Kanak Kanak Islam Terpadu Kota Padang - Sari, Siska Puspita; Safri, Edi; Wendry, Novizal (Institut Agama Islam Sumatera Barat Pariaman, 2024)
Children's education is something that really needs to be considered, so that they get knowledge that has the correct evidence. Therefore, educational materials for children also need to be checked to the maximum, especially in learning hadith given to children in kindergarten. It has been found that many of the hadith materials given to students are derived from hadith that are dhaif and not even from the Prophet Muhammad's hadith, but are considered as a hadith. The purpose of this research is to trace the hadith materials taught in the Integrated Islamic Kindergarten Schools in Padang City that are in accordance with the hadith delivered by the Prophet Muhammad. The research method used a qualitative method in the form of library research. This research model is a study of takhrij hadith related to hadith learning materials about ethics at the Integrated Islamic Kindergarten School in Padang City. The results of the research findings can be concluded that first, there are many errors in the writing of hadith learning materials due to the infiltration of hadith and writing does not refer to the books of hadith. Secondly, the author's search to the hadith books for 25 hadith that have been taught to students of Integrated Islamic Kindergartens in Padang City. The hadiths contained in the learning materials of the students of the Integrated Islamic Kindergarten in Padang City consist of 16 hadiths of saheeh quality, 2 hadiths of hasan quality, 1 hadith of Hasan saheeh status and 1 hadith of hasan gharib status, 3 hadiths of Maudhu' status and 2 hadiths whose source books were not found based on the snippets of matan taught.